Immediate Effects of Whole Body Vibration on Proprioception and Upper Extremity Reaction Speed in Young Adult Students - Maden, Cagtay; Yiğit, Sedat; Karabulut, Demet; Kavak, Fatma Betül; Yıldırım, Hatice; Elpeze, Gönül; Göl, Mehmet (La Medicina del Lavoro, 2024)
Background: There is limited information on the immediate effects of whole-body vibration (WBV) on the upper limb. This study aims to determine the immediate effects of WBV on reaction speed and proprioception in young adult students’ upper extremities. Methods: In total, 62 students participated in the study. WBV was applied to the participants, and its immediate effects on proprioception and upper extremity reaction speed were examined. Participants’ proprioception and perception of joint position at 30-60 degrees of shoulder flexion, shoulder abduction, and elbow flexion angles were measured with absolute error degrees. Reaction rates were evaluated with the Ruler-Drop Test and the mobile application SWAY. Results: A decrease was observed in the absolute error level of the participants’ joint position perception at 30-60 elbow and shoulder position degrees, measured after immediate WBV application (p <0.05). After the RDT application, a decrease in the length of catching the target was observed (p <0.05). The SWAY test determined that they moved the smartphone in a shorter time (p <0.05). Right and left RDT scores showed that the distance to catch the ruler was significantly lower in male individuals before the application. In comparison, the distance to catch the ruler was lower after the application (right/left p<0.05). Conclusions: The study found that applying WBV improved upper extremity proprioception perception and reaction speed in young adults. This information can guide clinicians in applying WBV to healthy individuals and those with symptoms.